MEMAKSIMALKAN KOMPETENSI SENAM LANTAI MELALUI METODE PRACTICE STYLE DENGAN CARD TASK DI SMAN 1 BUNGO - safrial, b (Jurnal Tunas Pendidikan, 2022)
This research was conducted because there are problems that arise in class XI MIPA SMAN 1 Bungo, namely students feel less interested in participating in headstand learning because they are afraid to do headstand exercises and do not understand the correct explanation of headstand movements. This research uses classroom action research method. In the implementation of the first cycle, there was one meeting and the second cycle was carried out in 1 meeting, where in each cycle there would be an increase in the headstand learning outcomes. The subjects of this study were students of class XI MIPA 2 SMAN 1 Bungo. Based on the results of the study, it was obtained the percentage of mastery learning in the first cycle, the skill aspect was 11.76% with an average score of 51.18, the attitude aspect was 58.82% with an average score of 73.53 and 64.71% of the knowledge aspect with an average score. -average 76.18. In the second cycle there was an increase to 70.59% skill aspect with an average value of 71.91, attitude aspect 76.47% with an average value of 76.47 and knowledge aspect 91.18% 83.53. Learning outcomes in the first cycle that can meet the KKM as many as 17.65% of the total students with an average score of 65.44 and in the second cycle increased to 76.5% of the total students with an average score of 76.76. Based on the results of the research above, it can be concluded that learning through the practical style method with task card media can improve learning outcomes for students in class XI MIPA SMAN 1 Bungo.